High frequency of cutaneous eruptions within the first year after allogeneic hematopoietic stem cell transplantation - Valentine Dambricourt; Adrien Bassompierre; Claire Le Calve; Léonardo Magro; David Beauvais; Micha Srour; Valérie Coiteux; Sarah Faiz; Benoît Catteau; Delphine Staumont‐Salle; Frédéric Dezoteux (Wiley, 2023)
Abstract Background The diagnosis and management of eruptions after hematopoietic cell transplantation (HCT) is a challenge due to their atypical clinical presentation and the biology biased by immunosuppression and graft. The diagnosis is therefore based on multiple grounds. Few studies have focused on the occurrence of a skin rash during the first year of transplantation. Objectives To assess the frequency of rashes in this period, as well as their differential diagnosis and multidisciplinary management. Methods We performed a retrospective monocentric descriptive study in the Department of Blood Diseases of Lille University Hospital. All patients who received allogeneic HCT between January 1, 2018, and December 31, 2019, were included. Results We included 196 patients with allogeneic HCT. Of these, 89 (45.4%) presented a skin rash during the first year after transplantation. Among them, 78.7% were diagnosed with acute graft versus host disease (GVHD), 6.7% chemotherapy toxicity, 4.5% chronic GVH, 2.2% of infectious origin and 1.1% drug hypersensitivity. The outcome was mainly favourable (74.2% experienced resolution). A skin biopsy was performed in 9% of cases. Viral polymerase chain reactions (PCRs) were positive in 7.1% of tested patients. Conclusions Our study revealed a high frequency of skin rashes in stem cell transplant patients, thus justifying the multidisciplinary management of these high‐risk patients, which require both dermatological and haematological early expert assessment.